Juridical analysis of the settlement of the transfer of receivables by Cessie Between UOB Bank and Linda Soetanto - Ekaratri, Azkia; Gunadi, Ariawan (Trigin Publisher, 2024)
The transfer of receivables by cessie between UOB Bank and Mrs. Linda still raises issues related to legal issues and the settlement of the cessie lawsuit. Legal Effects of Transfer of Receivables by Cessie Against Collateral that has been given Mortgage Rights Based on Court Decision No 370/Pdt.G/2019/PN Jkt.Pst and Civil Settlement of Transfer of Cessie Receivables in Court Based on Court Decision No 370/Pdt.G/2019/PN Jkt.Pst. Using normative legal research methods with qualitative analysis by using primary and secondary legal materials conducted using literature studies and through a case approach. The results of the study illustrate that UOB bank as a creditor has the legal power of proof of the legal event of a transfer of receivables in cessie to Chyntia as a third party and also, in this case, UOB bank as a creditor has the power of proof to Mrs. Linda Soetanto as a debtor related to the transfer of receivables. The plaintiff's lawsuit cannot be accepted because the formality of the lawsuit is not perfect, therefore all costs incurred in this case are charged to Mrs. Linda as the plaintiff for Rp. 1,041,000. The settlement regarding the transfer of receivables by cessie is carried out between Cyntia as the new creditor as well as the holder of Mrs. Linda's receivables, so everything regarding the settlement of Mrs. Linda's credit, Cyntia has the right and obligation to execute against the object of collateral belonging to Mrs. Linda.